2003
DOI: 10.1063/1.1545162
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent characteristics of poly(3 hexylthiophene)-fullerene based heterojunction organic solar cells

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. Electrical and optical properties of poly͑3-hexylthiophene-2.5diyl͒ ͑P3HT͒ used as the main component in a polymer/fullerene solar cell were studied. From the study of space-charge limited current behavior of indium-tin-oxide ͑ITO͒/P3HT/Au hole-only devices, the hole mobility and density were estimated to range from 1.4ϫ10 Ϫ6 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
156
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(177 citation statements)
references
References 16 publications
18
156
1
2
Order By: Relevance
“…36 An increase of the cell temperature from 9 • C to 48 • C decreased V oc by about 9% from 1.11 to 1.01 V and increased J sc by about 7% from 5.81mA cm −2 to 6.21mA cm −2 . The obtained temperature coefficient dV oc /dT ≈ −2.6 mV K −1 for the material system ID583/C 60 was larger than values for other organic D/A systems [37][38][39] and comparable to the values found in past generations of silicon pn-junction solar cells. 40 In contrast to the pronounced influence of the cell thickness, the cell temperature had nearly no influence on the approximately linear photocurrent-voltage response in the voltage range between 0.3 and 0.9 V.…”
Section: Influence Of the Cell Thicknessmentioning
confidence: 79%
“…36 An increase of the cell temperature from 9 • C to 48 • C decreased V oc by about 9% from 1.11 to 1.01 V and increased J sc by about 7% from 5.81mA cm −2 to 6.21mA cm −2 . The obtained temperature coefficient dV oc /dT ≈ −2.6 mV K −1 for the material system ID583/C 60 was larger than values for other organic D/A systems [37][38][39] and comparable to the values found in past generations of silicon pn-junction solar cells. 40 In contrast to the pronounced influence of the cell thickness, the cell temperature had nearly no influence on the approximately linear photocurrent-voltage response in the voltage range between 0.3 and 0.9 V.…”
Section: Influence Of the Cell Thicknessmentioning
confidence: 79%
“…In bulk heterojunction solar cells using poly͑3-hexylthiophene͒ doped ͓6:6͔-phenyl-C61 butyric acid methyl ester ͑P3HT:PCBM͒, morphology control of active layer is very important. Additionally, through thermal annealing of P3HT:PCBM blend devices, the external quantum efficiency and power conversion efficiency of these cells are dramatically increased; 16 In these cases, a power conversion efficiency for a P3HT/PCBM blend system as high as about 3% has been reported. 17 Many studies have shown that poor morphology, i.e., the severe phase separation of the active layer, is a key factor in loss of device performance.…”
mentioning
confidence: 99%
“…͑2͒ has also been applied to explain the temperature dependence of V oc of polymer:fullerene bulk heterojunction solar cells. 5,6 However, it is not clear whether such an analysis in terms of an ideal solar cell is justified for the case of polymer:fullerene bulk heterojunctions. Moreover, the fact that both J sc and J s are also temperature dependent further complicates the applicability of Eq.…”
mentioning
confidence: 99%
“…Equation ͑6͒ can be rewritten in terms of the quasi-Fermi levels as 6 TABLE I. Overview of ideality factors n obtained from …”
mentioning
confidence: 99%